Stress corrosion cracking of pipelines - Cheng, Y. Frank (Wiley Series in Corrosion, 2013)
Pipelines sit at the heart of the global economy. When they are in good working order, they deliver fuel to meet the ever-growing demand for energy around the world. When they fail due to stress corrosion cracking, they can wreak environmental havoc. This book skillfully explains the fundamental science and engineering of pipeline stress corrosion cracking based on the latest research findings and actual case histories. The author explains how and why pipelines fall prey to stress corrosion cracking and then offers tested and proven strategies for preventing, detecting, and monitoring it in order to prevent pipeline failure. This book begins with a brief introduction and then explores general principals of stress corrosion cracking, including two detailed case studies of pipeline failure. Next, the author covers: Near-neutral pH stress corrosion cracking of pipelines; High pH stress corrosion cracking of pipelines; Stress corrosion cracking of pipelines in acidic soil environments; Stress corrosion cracking at pipeline welds; Stress corrosion cracking of high-strength pipeline steels.